(untitled) (REMUNOM, 2024)
Klebsiella pneumoniae is an enterobacteria that affects the respiratory tract, urinary tract and wounds, the mouth being its main portal of entry and pneumonia being its main form of infection. Individuals in intensive care units, and individual who are immunologically injured are the most susceptible to contamination by this highly antimicrobial-resistant microorganism. Due to the genes that encode many resistance mechanisms to Ampcillin and other antibiotics, it became necessary to study ways to enhance the action of these medications, including the association with phytotherapic products. The present study aims to evaluate the effect of the association of Juniperus communis essential oil with Ampcillin and Cephalotin against strains of Klebsiella pneumoniae. To fulfill the study, it was used the diffusion technique using filter paper discs in which the Ampcillin and Cephalothin discs were placed in Agar Muller-Hinton environment inoculated with bacterial suspension and then soaked in the diluted and solubilized essential oil. Simultaneously, for each strain (KP101, KP 103, KP 104 and KP 105) it was also made a control study for subsequent comparison of the formation of inhibition halos. Finally, the associations presented antagonistic and indifferent effects for most strains, with the exception of the association with Cephalothin, which exhibited a synergistic effect against KP 104. This study presented a partially effective result, indicating the antibacterial potential of the natural product evaluated and revealing the inefficiency of Ampicillin in inhibiting the growth of Klebsiella pneumoniae.